Analysis of skin and corneal fiber electrodes for electroretinogram assessments in patients with major depressive disorder - Nickel, Kathrin; Tebartz van Elst, Ludger; Beringer, Malina; Endres, Dominique; Runge, Kimon; Maier, Simon; Küchlin, Sebastian; Bach, Michael; Domschke, Katharina; Heinrich, Sven P.; Friedel, Evelyn B. N. (Frontiers in Neuroscience, 2024)
BackgroundElectroretinograms (ERG) are usually recorded with non-invasive corneal electrodes, requiring direct contact with the ocular surface. However, corneal electrode application is not tolerated by some individuals. The advent of handheld ERG devices has facilitated the use of skin electrodes for ERG measurements. Skin electrodes do not require corneal contact and thus enhance patient comfort, simplify the attachment process, and reduce preparation time, which is particularly beneficial for clinical psychiatric research. Nevertheless, due to the different attachment methods, ERG amplitudes recorded with skin compared to corneal electrodes are considerably smaller. However, comparative data on ERGs recorded with skin vs. corneal electrodes in psychiatric populations are currently lacking.Materials and methodsWe recorded flash electroretinograms of 57 healthy controls (HC) and 30 patients with a major depressive disorder (MDD) using both sensor strip skin and corneal electrodes with the handheld RETeval® device.ResultsThe significant reduction in both the amplitude and peak time of the a-wave in MDD when using sensor strip skin electrodes could not be replicated with corneal electrodes. Comparing both electrode types in HC revealed a fair correlation between sensor strip and corneal electrodes for a- and b-wave amplitudes and a moderate correlation for a- and b-wave peak times.ConclusionIn addition to being better tolerated, sensor strip skin electrodes appear to be more effective than corneal electrodes in detecting ERG alterations in patients with MDD when using the RETeval® device, making them a promising alternative to traditional corneal electrodes.